Developing countries and humanitarian intervention in international society after the Cold War - Virk, K (2010)
This thesis examines the policies, positions, and perspectives of developing countries on the emerging norm of humanitarian intervention after the Cold War, focusing on the period between 1991 and 2001. In doing so, it questions the role of opposition that conventional wisdom has allotted to them as parochial defenders of sovereignty. Instead, the thesis reveals variation and complexity, which militates against defining the South, or the issues that humanitarian intervention raises, in simplistic either-or terms. Part I draws on insights about ‘sovereignty as what states make of it’ to break the classic pluralism-solidarism impasse that has otherwise stymied the conversation on humanitarian intervention and confined the South as a whole to a ‘black box’ labelled rejectionism. It reconstructs the empirical record of developing countries at large on six cases of military intervention (northern Iraq, Somalia, Haiti, Sierra Leone, Kosovo, and East Timor), revealing variation that defies easy categorization. It also charts a cumulative and dynamic trend within the South towards a grey area between pluralism and solidarism that shows how these were not diametrically opposed positions. Following from that, Part II looks in-depth at India and Argentina. Whereas Argentina accepted the idea of humanitarian intervention, India remained reluctant to countenance it and persistently objected to the development of a new rule in its favour. Part II argues that the level of congruence between the emerging norm and the two countries’ prevailing values, aspirations, and historically constructed ways of thinking played a key role in determining the different levels of acceptance that the idea found with them. Part III delves deeper into the substance of their views. It shows how neither country constructed mutually exclusive choices between pluralism and solidarism, sovereignty and human rights, and intervention and non-intervention. Rather, both exhibited an acute awareness of the dilemmas of protecting human rights in a society of states, and a wariness of yes-no answers. Cumulatively, this thesis thus points away from thinking about the South itself as a given category with clear, shared or pre-determined ideas, and towards a more nuanced and inclusive conversation on humanitarian intervention.